Influence of body mass index on induction of labor: A historical cohort study - Dammer, Ulf; Bogner, Roswitha; Weiss, Christel; Faschingbauer, Florian; Pretscher, Jutta; Beckmann, Matthias; Suetterlin, Marc; Kehl, Sven (Journal of Obstetrics and Gynaecology Research, 2018)
AIM: We aimed to determine the influence of body mass index (BMI) on induction of labor. METHODS: In this historical multicenter cohort study, 2122 labor inductions were analyzed. Women were divided into four groups according to their body mass index (BMI): BMI < 30 (normal group [NG]), 30 ≤ BMI < 35 (group 1 [G1]), 35 ≤ BMI < 40 (group 2 [G2]), and BMI ≥ 40 (group 3 [G3]). The primary outcome measure was the induction-to-delivery interval. The secondary outcome parameter was, among others, the rate of cesarean section. RESULTS: A total of 1113 inductions of labor were analyzed in the NG, 610 in G1, 239 in G2, and 160 in G3. The induction-to-delivery interval was shorter in the NG compared to G1 (mean values 1550 min vs 1669 min, P = 0.0406), G2 (1745 min, P = 0.0294), and G3 (1899 min, P = 0.0008). The cesarean section rate was significantly higher in G1-G3 (G1: 30.8%, P < 0.001; G2: 30.5%, P < 0.0067; G3: 42.5%, P < 0.0001) compared to the NG (21.8%). There were more vaginal deliveries within 48 h in the NG (84%) compared to G1-G3 (78%, P = 0.0186; 75%, P = 0.0049; 75%, P = 0.0329). However, these findings could mainly be seen in nulliparous women when stratifying for parity. Multivariable analysis showed that high BMI increased the induction-to-delivery interval whereas high parity, gestational age, and Bishop score decreased it. CONCLUSION: An increased body mass index has a negative impact on induction of labor at term, especially in nulliparous women.
EVALuna2:209950